The impact of colour and light on children with autism in interior spaces from an architectural point of view. (14th February 2019) - Shareef, Sardar S.; Farivarsadri, Guita
The primary aim of this study is to investigate the role of 'colour and light' on the perception of children with autism and to indicate the most preferred colours and lights for an interior environment for them. Related documents were reviewed from studies published in journals, books, internet sources etc., also data collation was done in a local special learning school in the city of Famagusta; Northern Cyprus called 'Special Education Centre' (Özel Eğitim Merkezi). The centre cares and treats children with autism. Finally, in the study, a comparison between literature review outcomes and the results from the field study was done. Consequently a 'checklist' was prepared as a guiding light for architects and interior designers to help them in the design of living spaces for people who have autism.